Healing of cracks in freshwater, saline and sea ice, 2020-2022 - Andrii Murdza; Erland Schulson; Carl Renshaw (Arctic Data Center)
The combination of a decrease of the ice coverage on the Arctic Ocean, an increase of the amplitude of ocean waves, and damage due to the daily increases and decreases in temperature may lead to the breakup of ice cover. Of interest, therefore, is the strength of ice that was thermally damaged during diurnal temperature cycles. To understand the behavior of ice under these conditions, we conducted new systematic experiments on freshwater and sea ice in the present study, where the ice was cracked by thermal shocking. The cracks initially weakened the ice but within a short period of time, the ice strength returned to its original value. This observation of crack healing is attributed to the formation of a thin liquid water layer on opposing crack surfaces which aid to its freezing as contact is made during warming. The effect of crack healing may help to avoid ice breakup. Sea ice was collected in the Beaufort Sea during winter 2020, while saline ice and freshwater ice were produced in the laboratory.